Refusing to Wait: Just-in-Time Teaching - Cahill, Ann J.; Mould, Tom (Radical Teacher, 2018)
Shortly after the presidential election of 2016, a group of faculty and staff at Elon University committed to developing and offering a one-credit course designed to provide students with intellectual and practical skills that would be useful in facing contemporary social and political challenges. This article describes the process of developing the course, its structure and content, and its effects on the students, faculty, and staff who participated in it. The article also discusses strengths and weaknesses of the course design as a means of helping to ensure the success of any future endeavors. The course, which eventually came to be titled “Refusing to Wait: Intellectual and Practical Resources for Troubled Times,” is an example of how institutions of higher education can respond quickly and effectively to political developments, while keeping student learning at the center of their mission.